2022
DOI: 10.1590/0074-02760220005
|View full text |Cite
|
Sign up to set email alerts
|

Increased angiogenesis parallels cardiac tissue remodelling in experimental acute Trypanosoma cruzi infection

Abstract: BACKGROUND Angiogenesis has been implicated in tissue injury in several noninfectious diseases, but its role in Chagas disease (CD) physiopathology is unclear.OBJECTIVES The present study aimed to investigate the effect of Trypanosoma cruzi infection on cardiac angiogenesis during the acute phase of experimental CD. METHODSThe signalling pathway involved in blood vessel formation and cardiac remodelling was evaluated in Swiss Webster mice infected with the Y strain of T. cruzi. The levels of molecules involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…As stated earlier, it is possible that a prolonged destabilization of the endothelial barrier forged via the activation of the KKS/DABK/B1R pathway might translate into reciprocal benefits to the host/parasite relationship [13,14]. Nisimura et al have recently reported that angiogenesis parallels cardiac tissue remodeling in mice acutely infected by T. cruzi [64]. Interestingly in this context, we recently showed evidence that microvascular permeability is subtly increased at the early stages of infection in the hamster cheek pouch, preceding the vascular remodeling process that underlies angiogenesis [9].…”
Section: Discussionmentioning
confidence: 95%
“…As stated earlier, it is possible that a prolonged destabilization of the endothelial barrier forged via the activation of the KKS/DABK/B1R pathway might translate into reciprocal benefits to the host/parasite relationship [13,14]. Nisimura et al have recently reported that angiogenesis parallels cardiac tissue remodeling in mice acutely infected by T. cruzi [64]. Interestingly in this context, we recently showed evidence that microvascular permeability is subtly increased at the early stages of infection in the hamster cheek pouch, preceding the vascular remodeling process that underlies angiogenesis [9].…”
Section: Discussionmentioning
confidence: 95%